2013
DOI: 10.2478/jwld-2013-0011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of sediments in Suchedniów reservoir / Rozkład osadów w zbiorniku Suchedniów

Abstract: The paper presents measurements of the amount, spatial distribution, grain size structure, density and the content of organic matter in sediments of Suchedniów reservoir. After 33 years of exploitation, the primary volume of the reservoir decreased by 78 thousand m3. Catchment area covered in 45% by forests is 83 km2. Mean annual water flow is estimated at 0.63 m3·s-1. Primary volume of the reservoir was 303 thousand m3 and its surface area - 21.4 ha. The greatest width of the reservoir is 490 m, distance from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Soil erosion due to water and wind results in the loss of valuable top soil and causes land degradation as well as environmental quality, water management and hydro-technical problems [BANASIK et al 2012;BANASIK, MITCHELL 2008;BĄK, DĄBKOWSKI 2013;BHATTARAI et al 2011;BOUCHELKIA et al 2014;KOWALCZYK, TWARDY 2012;MIODUSZEWSKI 2012;MITCHELL et al 2001]. There are different methods for soil conservation but biological methods in bare or degraded slopes need long time for establishment [ADEKALU et al 2007;CERDÀ 1999;SMETS et al 2008a;SPALEVIC et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Soil erosion due to water and wind results in the loss of valuable top soil and causes land degradation as well as environmental quality, water management and hydro-technical problems [BANASIK et al 2012;BANASIK, MITCHELL 2008;BĄK, DĄBKOWSKI 2013;BHATTARAI et al 2011;BOUCHELKIA et al 2014;KOWALCZYK, TWARDY 2012;MIODUSZEWSKI 2012;MITCHELL et al 2001]. There are different methods for soil conservation but biological methods in bare or degraded slopes need long time for establishment [ADEKALU et al 2007;CERDÀ 1999;SMETS et al 2008a;SPALEVIC et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Lai and Capart proposed a simple morphodynamic theory of reservoir deltas prograding over bedrock, which they verified through the development process of the delta in Wushe reservoir [10]. Taking the Suchedniów reservoir as an example, Łukasz BK studied the sediment distribution characteristics of this small reservoir and found that existing methods could not accurately predict the sediment distribution [11]. In recent years, with the development of computer technology, the simulation of reservoir sediment has become a research focus.…”
Section: Introductionmentioning
confidence: 99%
“…The grain size of sediment particles tends to decrease along the water flow direction, and in the inlet part of a reservoir higher volume of sediments are deposited than in the outlet part (Bak and Dabkowski, 2013;Jing, et al, 2013). The ST inside irrigation canal networks is designed for the deposition of fine particles, which account for a large portion of the total flow (up to 70%).…”
Section: Introductionmentioning
confidence: 99%